Nonspecific promises: Restitutive ’again’ and intensional transfer-of-possession verbs - Johnston, William (Proceedings of Sinn und Bedeutung, 2022)
In this paper I describe a novel pattern of infelicity, in which the restitutive reading of the adverbs again and back is infelicitous when combined with intensional ‘transfer-of- possesion’ verbs (e.g. promise, offer) that take nonspecific objects. I offer one possible analysis of this phenomenon under the so-called “‘re’-domain” framework of Zwarts (2019), a lexical analysis of the again ambiguity that describes the restitutive presupposition with reference to a semantic path. This predicts a key role for the theme of the modified event, leading to presupposition failure in cases where no unique theme can be identified.